Selective separation and concentration of antihypertensive peptides from rapeseed protein hydrolysate by electrodialysis with ultrafiltration membranes. (15th April 2016) - He, Rong; Girgih, Abraham T.; Rozoy, Elodie; Bazinet, Laurent; Ju, Xing-Rong; Aluko, Rotimi E.
Highlights: Rapeseed peptides were fractionated using electrodialysis with ultrafiltration membrane. Membrane fouling was not detected after 3 consecutive runs of the system. Yield of anionic peptides was higher than that of cationic peptides. The cationic peptides had stronger ACE and renin inhibitions than anionic peptides. The cationic peptides also had stronger blood pressure-lowering effect. Abstract: Rapeseed protein isolate was subjected to alcalase digestion to obtain a protein hydrolysate that was separated into peptide fractions using electrodialysis with ultrafiltration membrane (EDUF) technology. The EDUF process (6 h duration) led to isolation of three peptide fractions: anionic (recovered in KCl-1 compartment), cationic (recovered in KCl-2 compartment), and those that remained in the feed compartment, which was labeled final rapeseed protein hydrolysate (FRPH). As expected the KCl-1 peptides were enriched in negatively-charged (43.57%) while KCl-2 contained high contents of positively-charged (28.35%) amino acids. All the samples inhibited angiotensin converting enzyme (ACE) and renin activities in dose-dependent manner with original rapeseed protein hydrolysate having the least ACE-inhibitory IC50 value of 0.0932 ± 0.0037 mg/mL while FRPH and KCl-2 had least renin-inhibitory IC50 values of 0.47 ± 0.05 and 0.55 ± 0.06 mg/mL, respectively. Six hours after oral administration (100 mg/kg body weight) to spontaneously hypertensive rats, the FRPH produced the maximum systolic blood pressure reduction of −51 mmHg.